Risk of RBC alloimmunization in multiple myeloma patients treated by Daratumumab. Issue 2 (14th November 2019) - Ye, Zhan; Wolf, Laurie A.; Mettman, Daniel; Plapp, Fred V.
Abstract : Background: Daratumumab (DARA) is a human monoclonal antibody for the treatment of multiple myeloma (MM). DARA binds to CD38 on RBCs and interferes with detection of RBC alloantibodies. The objective of this study was to evaluate the risk of RBC alloimmunization in MM patients treated with DARA. Materials and methods: A retrospective study of the complete serological profile and transfusion history of 45 MM patients received transfusion and treated with DARA from July 2015 to December 2018 was undertaken. All cases with positive Ab screens were treated with DTT to identify RBC alloantibodies. RBC transfusion history was monitored between the first DARA dose to the last or extending to the first negative Ab screen after the last DARA dose if the Ab screen was ever positive. Forty‐six MM patients received transfusion but not DARA were studied as control group. Results: Totally 184 Ab screens were done on 45 patients transfused with ABO‐Rh compatible RBCs, phenotypically matched units or both. None of them showed detectable alloantibodies after DTT treatment. The duration of Ab screening positivity varied markedly, ranging from 25 days to 5 months after the last dose. Two of 46 patients in the control group had preexisting alloantibodies but no new alloantibodies were detected during study period. Conclusions: Our results indicate that the risk of forming new RBC alloantibodies after transfusion in MM patients treated with current regimens is very low and no DARA‐associated difference in the alloimmunization risk. No significant difference in alloimmunization is detected between ABO‐Rh compatible and phenotypically matched transfusion.